A cross-sectional study of autoantibody profiles in the Waikato systemic sclerosis cohort, New Zealand. Issue 11 (November 2015) - Chang, Winston; Schollum, Joanna; White, Douglas; Solanki, Kamal
Abstract The autoantibody profiles in New Zealand systemic sclerosis patients have not previously been reported. The aim of this study was to evaluate the autoantibody profiles of patients in the Waikato Hospital Systemic Sclerosis Clinic cohort. The EUROLINE (IgG) Systemic Sclerosis panel test kit (which tests for Scl-70, CENP-A, CENP-B, RP11, RP155, Fib, NOR90, Th/To, PM100, PM75, Ku, PDGFR and Ro-52) was selected for the purpose of this study. All patients attending the Waikato Hospital Systemic Sclerosis clinic were invited to participate. These patients were categorised by systemic sclerosis subtypes [1]. Results were compared with previously published data, including the EUSTAR database. Sixty patients (56 female) were recruited, with a median age of 61 years (range 29–81 years). Forty-one had limited cutaneous systemic sclerosis (lcSSc). Of these lcSSc patients, 31 (75.6 %) were positive for CENP-A and CENP-B (anti-centromere) antibodies, 12 (29.3 %) for Ro-52 antibodies, 5 (12.2 %) for RP11 and RP155, 4 (9.8 %) for Scl-70 and 1 (2.4 %) each for anti-Fib and Th/To antibodies. Fifteen patients had diffuse cutaneous systemic sclerosis (dcSSc), of which 7 patients (47.6 %) were positive for RP11 and RP155, 4 (26.7 %) for Scl-70. Three dcSSc patients did not have either of these two major antibodies, but of these 15 dcSSc patients, 4 patients (26.7 %) were positive also for Ro-52, 2 (13.3 %) for anti-Ku, and 1 (6.7 %) each for anti-Fib and NOR90. Four patients had overlap syndrome (OLS), 1 had CENP-A and CENP-B antibodies, 1 had Ro-52 autoantibodies 1 had anti-Ku antibodies. Three patients had no autoantibodies. This is the first study to look at the autoantibody profile of SSc patients in New Zealand. A higher prevalence of antibodies against centromere and RNA polymerase III was demonstrated in our group compared with the EUSTAR database suggesting that antibody prevalence may vary geographically.